Ralph W. Christie papers - Christie, Ralph W. (Ralph Waldo), 1893-1987.
Chiefly Christie's official correspondence as a commander of submarines during World War II. Includes material relating to Christie's efforts to have a medal of honor awarded to submarine commander Samuel David Dealey.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Dealey, Samuel David, -- 1906-1944.; United States. -- Navy -- Medals, badges, decorations, etc; World War, 1939-1945 -- Naval operations -- Submarine; Naval officers